Not Reconciled: Grey Matter (Ruhorahoza 2011) and the Lacunae of Post-genocide Rwandan Cinema. - Broderick, Mick (Critical Arts: A South-North Journal of Cultural & Media Studies, 2017)
In the two decades following the Rwandan genocide, a small number of feature films have attempted to represent aspects of the traumatic national experience of this mass violence. Apart from a few documentaries, official Rwandan government efforts towards national reconciliation remain largely absent in indigenous feature films, most of which treat their subject matter via conventional, social realist narratives. This essay assesses Kivu Ruhorahoza’s formidable debut production, Grey Matter (2011), and its aesthetic echoes of earlier modernist European cinema’s lacunary evocation of the Holocaust and the trauma of World War Two.